Yevgeny Lhamatsyrenovich Choinzonov (to 60th birthday) - edition magazine (Бюллетень сибирской медицины)
The biography of famous native scientist, doctor of medical sciences, academician of the Russian Academy of Medical Sciences, Director of the Cancer Research Institute of Siberian Branch of the Russian Academy of Medical Sciences, head of Oncology Сhair of Siberian State Medical University Professor Ye.L. Choinzonov has been prezented. The main directions of scientific and public activity of the scientist are shown.